DETECTION PROTECTIVE ANTIGEN WITH MONOCLONAL ANTIBODY OF PASTEURELLA MULTOCIDA DOMPU ISOLATE - Sri Murwani; Widya Asmara (Jurnal Sain Veteriner, 1999)
Monoclonal antibodies can be used as specific probes for molecular structure such as drugs, hormones, receptor for hormones, or any other biologycally derived or biology-cally active materials. The potential usefulness of monoclonal antibodies is in almost every field of biology and medicine.The study was carried out to produced monoclonal antibodies against outer membrane protein (OMP) Pasteurella multocida isolat Dompu, which can be used to isolate imunogenic OMP fractions.Three monoclonal antibodies which specifically react with OMP fraction of Pasteurella multocida isolat Dompu were obtained previously. Those monoclonal antibodies were produced in Balb/c mouse. The antibodies production were measured by ELISA and were purified by affinity chromatograPhy.The monoclonal antibody were injected intraperitoneally into group of five rats. Two additional groups of five rats were injected with immune mouse serum and normal mouse serum, which served as a positive and negative controls respectively. All rats were challenged with 1 ml lethal dose of Pasteurella multocida 24 hours after the antibody injection.The outer membrane protein was separated 12,5% SDS-PAGE. The region of gel containing the appropiate antigens (PI, P2, P3) were excised. Protein antigen was mixed with incomplete Freund's adjuvant (IFA) and injected intramuscu-lary into group of five rats at dose 0,2 ml per mouse. Two additional groups were injected with gel in IFA and OMP and IFA as a positive and negative controls. Each treated mouse and control was immunized four times, at weekly interval. Two weeks after final immunization rat were bled and their antibodies productions were measured with ELISA. All mice were then challenged with lethal dose of Pasteurella multocida.The result indicated that eventhough immungenic the PI, P2, P3 OMP fraction individually were not able to induce protective antibody.